Bovine milk production in Campeche: prospects and challenges for rural producers' development (Agro Productividad, 2021)
Objective: To characterize at the municipal level the productivity of the bovine-milk sector in the state of Campeche, Mexico; to determine the profitability of the sector and to propose improvement schemes in order to add value to the commercialization of the product.Design/Methodology/Approach: From the Agricultural and Fisheries Information System, the following variables were obtained: Production (thousands of L), Price ($ L-1) and Value of Production (thousands of $) from 2006 to 2018. Through multivariate statistics and analyses, the profitability of the bovine-milk sector from 2013-2018 compared to 2007-2012 was determined. The analyses were completed by an interview with 12 milk producers who gave added value through the manufacture of cheeses.Results: A drop in profitability (-8.8%) was found in the sector from 2013-2018 compared to 2007-2012, despite the increase in production of 6.2% that did not compensate for the fall in prices (-14.2%). The regions with the highest productivity were located from the center to the south of the state: Champotón (24.62%), Escárcega (17.36%), and Campeche (16.63%).Study Limitations/Implications: Adding value to the milk commodity is a priority need in the short term, to avoid abandoning the activity, which could compromise the economy of rural producers.Findings/Conclusions: The Mennonite settlements in Campeche have managed to add value to the bovine-milk sector through the manufacture and sale of artisan cheeses. However, the great challenge of the sector is the revaluation of artisan cheeses with market strategies that encourage the consumption of local resources in a context of globalization.